Sensitivity to heat: A comparative study of Phoenix, Arizona and Chicago, Illinois (2003-2006) - CHUANG, Wen-Ching (Institutional Knowledge at Singapore Management University, 2013)
Research on how heat impacts human health has increased as climate change threatens to raise temperatures to new extremes. Excessive heat exposure increases death rates, as well as rates of nonfatal, adverse health outcomes. This study used the negative binomial regression model to examine the relationship between daily maximum temperature, heat index, and heat-related emergency calls in Phoenix, Arizona and Chicago, Illinois, from 2003 to 2006. Using model results, we estimated call volumes in a warmer climate, with temperature increase from 1 to 5.5 C. We found that: (1) heat-stress calls increase sharply when the temperature exceeds about 35 C in Chicago and in 45 C Phoenix; (2) warmer climate could seriously threaten human health and existing emergency response system in Chicago more than in Phoenix. Policies to reduce heat impacts in Phoenix should focus on reducing prolonged heat exposure, while Chicago should build a strong earlywarning system for extreme heat events and provide sufficient resources and infrastructure to mitigate heat stress during those events.